Stock Prices and Financial Fundamentals in Indonesia’s Technology Sector during 2023–2024 - Andre Felipe Wijaya; Imanuriea Annisa Putri Putri (Universitas Negeri Padang, 2026)
Purpose – This research seeks to examine the influence of net profit margin (NPM), earnings per share (EPS), and price to earnings ratio (PER) on Indonesian stock prices. Using the signaling theory framework, an increase in these three ratios is viewed as positive information that can reduce information asymmetry and build investor optimism regarding a company's fundamentals and growth prospects. Design/methodology/approach – The population of this study consists of 47 technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 observation period. This research sample was selected using a purposive sampling technique to ensure that only firms meeting the predetermined research criteria were included, thereby enhancing the relevance and reliability of the data analyzed. Findings – The results show that NPM, EPS, and PER have a positive and significant influence on stock price. Originality/value – Previous studies on the relationship between financial ratios and stock prices have produced inconsistent findings, particularly regarding EPS and PER. In addition, empirical evidence focusing specifically on Indonesia’s technology sector remains limited. This study addresses this gap by examining the influence of Net Profit Margin, Earnings Per Share, and Price to Earnings Ratio on stock prices of technology companies listed on the Indonesia Stock Exchange during the 2023–2024 period. Research limitations/implications – This study has several limitations. The analyst focuses only on technology firms listed on the Indonesia Stock Exchange, which restricts the generalizability of the result to other industries. Future studies may also consider including additional financial indicators or expanding the research scope to gain a more comprehensive view of stock price determinants in the technology sector. Article Type: Research paper